PREDIKSI LUASAN AREA TERPAPAR TSS DARI KEGIATAN DREDGING PADA ALUR PEMASANGAN PIPA RC-06 DI ESTUARI DELTA MAHAKAM - I Wayan Nurjaya; Andri Purwandani (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
In general, natural resources capable of generating foreign exchange, such as: gas, petroleum and various other minerals are found in locations that have high productivity. Conditions of waters that have high productivity serves to support the sustainability of biological resources (e.g.: fish, mangroves, seagrass beds, seaweed and coral reefs). The government in this case the Ministry of Environment and Forestry (formerly the Ministry of the Environment) actually has made the signs of a rule that must be met by business actors who conduct activities in sensitive areas to environmental changes. PT. Total E & P Indonesia (TEPI) located in Balikpapan has long been engaged in exploration and exploitation of oil and gas in the Mahakam Delta. The large flow of branches of the Mahakam River empties into the Mahakam Delta provides a promising business opportunity for the farmers to open their business. While TEPI has oil wells are scattered in the delta area, pipelines are needed to collect the oil from the wells to the processing site. Because of the large number of streams causing many oil and gas pipes to cross the river (river cross pipes) that require special handling and meet the standards of technical rules and environment set by the government to be safe from passing boats or fishing boats that pass at the location. This study was conducted to predict the extent of exposed areas of exposure, especially the TSS concentration generated from the dredging activities in the pipeline. The simulation results show that the area of impact (TSS> 80 mg / L) is 74275.13 m2 dominantly moving westward from the dredging location (RC-06 = River Crossing Pipe No. 6). The farthest distance of the affected river body (TSS> 80 mg / L) to the west is 557.00 m from RC-06. The farthest distance of the affected river body (TSS> 80 mg / L) to the northeast is 240.81 m from RC-06. The farthest distance of the affected river body (TSS> 80 mg / L) to the southeast is 216.98 m from the RC-06 location. There is no water mass with TSS> 80 mg / L entering the pond. Sedimentation due to dredging activities is not accumulated and has no impact on shrimp farming business. The results of this study is expected to make a scientific basis in helping solve the problem of compensation requested by the farmers to TEPI due to decreased tambak production.